Propylthiouracil-induced histological changes in the placenta of swiss albino mice - Samta Tiwari; S K Pandey (Wolters Kluwer Medknow Publications, 2020)
Introduction: Propylthiouracil, an antithyroid drug, is used to treat hyperthyroidism in early pregnancy as drug of choice. Maternal and fetal morbidities and mortalities occur, if hyperthyroidism is not treated during pregnancy. Aim: The teratogenic potential of propylthiouracil is studied by observing the placental changes in Swiss albino mice, in the light of present research. Materials and Methods: 100 mg/kg body weight/day of propylthiouracil was given orally to pregnant Swiss albino mice (treated group) during early gestational period (6, 7, and 8th days of gestation), while control pregnant mice were given the same volume of distilled water orally for the same duration. The pregnant mice of all groups were sacrificed on 18th day of gestation and placentae were collected. The placentae were grossly examined, formalin fixed, and processed for histological study with H and E staining. Results: Histological examination shows edematous spaces and degenerated normal architecture of the various zones, i.e., labyrinthine, junctional, and basal zones. There was increase in the thickness of chorioallantoic plate and degeneration of giant cell trophoblasts and sinusoids. Conclusion: It was found that the propylthiouracil had a teratogenic effect; therefore, it should be used cautiously during pregnancy to avoid risk of congenital malformations.